Kazus Alecka Bourne’a a konstytucyjne zasady ochrony życia i zdrowia - Szudejko, Piotr (Studia Prawa Publicznego, 2021)
The article presents the case of Dr. Aleck Bourne, which the author proposes to include in the catalog of borderline cases constituting the basis for in-depth discussions on ethical and legal aspects of human life with regard to the development of biology and medicine. The starting point is the presentation of the worldwide models for regulating the practice of abortion as well as the Polish regulation, together with a discussion on the role of the Constitutional Tribunal in shaping current legal provisions. The author notes that the interpretation of the right to life adopted by the Tribunal encourages the repeal of the indication model and the introduction of a complete ban on abortion, which will have significant consequences for ordinary legislation. Apart from describing the facts in the Bourne case, the strategy adopted by the defense and the sentence itself, the possible further areas of considerations regarding the limits of permissibility of termination of pregnancy have been signaled. Then, the conclusions resulting from legal analysis of the case were transferred to the exegesis of the constitutional principles of the right to life and the right to healthcare. Their constitutional form, interpretation resulting from the rulings of the Constitutional Tribunal and the ordinary legislation have been presented. The author indicates the main terminological deficiencies identified in this respect: the lack of any definition of the beginning of a human being, the existence of two separate criteria for determining death, which could lead to different results and the lack of an unambiguous definition of disease adopted by the legislator. Based on the concepts presented in the case, the right to healthcare has been defined as a legal right resulting from the right to life. The final thesis is that there are no grounds for hierarchizing these rights, as they are intertwined in content and function.